Association between serum albumin levels and the incidence of pedal edema in normotensive pregnant women - Jahan, Esmat; Holy, Mirza Farzana; Al Maruf, M. Abdullah; Akther, Nasima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Pedal edema is a common clinical condition during pregnancy, often associated with hypertensive disorders. However, its occurrence in normotensive pregnant women and its relationship with serum albumin levels remain underexplored. This study investigates the association between serum albumin levels and pedal edema while examining the potential influence of age, parity, and BMI in normotensive pregnancies. Methods: A hospital-based observational study was conducted on 100 normotensive pregnant women aged 20–40 years. Data on demographic details, obstetric history, and clinical parameters were collected. Serum albumin levels were measured in the third trimester and classified as normal (>3.5 g/dl) or low (≤3.5 g/dl). Pedal edema was assessed clinically. Statistical analysis was performed using chi-square tests, with a p value <0.05 considered significant. Results: Among the study population, 71.4% of participants with low serum albumin levels (≤3.5 g/dL) experienced pedal edema compared to 23.1% of those with normal levels (>3.5 g/dl) (p=0.012). Age, parity, and BMI were not significantly associated with the incidence of pedal edema (p>0.05). Underweight participants showed a higher prevalence of edema (50%) compared to those with normal (33.3%) and overweight BMI (33.3%). Conclusion: Low serum albumin levels are significantly associated with pedal edema in normotensive pregnant women, highlighting the importance of albumin monitoring during antenatal care. Addressing hypoalbuminemia may improve maternal health outcomes, particularly in resource-limited settings.